Strategic Sodium Reduction Initiative Reduces Sodium in Meals Served at Older Adult Congregate Meal Program Sites. Issue 2 (3rd April 2022) - Ullevig, Sarah L.; Spitsen, Ellen; Heine, Anne C.; Balarin, Ashton; Uc, Eliani; Shields, Kathleen; Sosa, Erica T.
Abstract: Excessive sodium consumption is a public health issue and congregate meal programs provide a unique opportunity to reduce sodium served to a large, at-risk population. A Sodium Reduction Initiative (SRI) was implemented in a congregate meal program that serves over 3, 000 older adults. Nutrient analyses conducted at baseline and post-intervention were used to calculate average sodium reduction and the number of low sodium foods; targeted foods were categorized by strategy. Customer satisfaction surveys were collected at baseline and 3- and 6-months post-intervention. Kruskal Wallis and analysis of variance were used to compare sodium reduction differences. Chi-square analysis determined associations among strategies. The SRI impacted 55 foods, low sodium foods increased by 22%, and the average sodium per menu cycle was reduced by 21%. Replacement with a lower sodium food was the most frequently used strategy and had the largest sodium reduction. Sauces and main entrees were most frequently impacted, and thirteen ingredients accounted for 75% of all reduced-sodium foods. Over 50% of the 1, 424 survey respondents consumed the reduced-sodium foods and food satisfaction remained stable from baseline to post-intervention. Congregate meals programs that target commonly used foods and key ingredients can significantly reduce sodium served to older adults.